La Crise de 19 a. C. et ses conséquences - Jonquieres, Céline de (Gerión. Revista de Historia Antigua, 2005)
The determination of M. Egnatius Rufus to aspire to the consulate for the year 19 a.C., with the support from a part the populus romanus, called into question the consensus which maked it possible for Augustus to be the Princeps. This situation illustrated the tensions which existed around the creation of the new regime. So that its capacity cannot be called into Auguste question decided to control personally the principal means of political ideology and to set up a dynastic policy.
Keywords: Augustus; consensus; Principate; ideology; populus